2009
DOI: 10.1111/j.1525-1594.2009.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Plasma Exchange in Patients With Severe Hypertriglyceridemia: A Multicenter Study

Abstract: Extremely high plasma triglyceride (TG) concentration is a recognized risk factor for acute pancreatitis (AP). In order to evaluate the therapeutic efficacy of plasma-exchange plasmapheresis in treating patients with severe hypertriglyceridemia (sHTG), 17 patients who had not responded to conventional medical therapy (fat-free diet plus pharmaceutical interventions) were referred for therapeutic plasma exchange (TPE) in a multicenter frame case series study. Two hundred seventeen TPE sessions were performed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 30 publications
(26 reference statements)
2
48
0
4
Order By: Relevance
“…Case studies, 37,38 including a multicenter series, have indicated that TPE is a safe, rapid, and highly effective intervention for emergency management of severe hypertriglyceridemia, effectively preventing related complications. Using TPE in patients with hypertriglycerid emia markedly reduces the serum level of triglycerides, allowing timely measurement of serum levels of electrolytes and reducing the risk for acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies, 37,38 including a multicenter series, have indicated that TPE is a safe, rapid, and highly effective intervention for emergency management of severe hypertriglyceridemia, effectively preventing related complications. Using TPE in patients with hypertriglycerid emia markedly reduces the serum level of triglycerides, allowing timely measurement of serum levels of electrolytes and reducing the risk for acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown a 41% (1,406 to 682 mg/dL) decrease in serum triglycerides after 1 session of apheresis alone [43]. Several studies have shown that apheresis can significantly decrease serum triglycerides and cause both clinical and laboratory improvement when conservative treatment with diet and pharmaceutical drugs fail [30,[44][45][46]. All these studies also stress the importance of performing apheresis as soon as possible to maximize therapeutic benefit.…”
Section: Intravenous Insulin ± Heparinmentioning
confidence: 99%
“…Iako se hipertrigliceridemija u dislipidemijskom pankreatitisu povremeno spontano koriguje, i to značajno sporije (neunošenjem hrane oralnim putem), veoma je značajna efikasna akutna i hronična kontrola nivoa Tg (najbolje <5mmol/L), kako zbog umanjenja ozbiljnosti i složenosti aktuelnog ataka pankreatitisa, tako i zbog prevencije kasnijih, rekurentnih ataka 4,6,9 . Iako su tretmani akutnih dislipidemijskih pankreatitisa složeni, oni pored intenzivnog suportivno-simptomatskog tretmana, uključuju heparinizaciju, intravensku primenu insulina, kao i TIP, dok se hronični tretman nastavlja trajnim higijensko-dijetetskim režimom i primenom fibrata [5][6][7][8] . TIP je za indikaciju dislipidemijskog pankreatitisa svrstana u treću kategoriju bolesti kada se procedura koristi kao adjuvantna terapija.…”
Section: Diskusijaunclassified